DAMPAK TANAMAN NILAM TERHADAP SOSIAL EKONOMI PETANI DI DESA KATANGANA KECAMATAN TIWORO SELATAN KABUPATEN MUNA BARAT - Hasmawati, Waode; Batia, La (Jurnal Penelitian Pendidikan Sejarah UHO, 2020)
ABSTRACT: The objectives of this study were: 1) To describe the development of patchouli cultivation in Katangana Village, Tiworo Selatan District, West Muna Regency, 2) To describe the impact on the socioeconomic impact of patchouli farming communities in Katangana Village, Tiworo Selatan District, West Muna Regency. This type of research is descriptive qualitative. This type of qualitative research with the following stages: 1) data collection techniques consist of several parts, namely: interviews, direct observation, and documentation; 2) data analysis technique consists of several parts, namely: data reduction, data presentation, and drawing conclusions; 3) data validity consists of extending observations, increasing persistence, and triangulation. Based on the research results that: 1) The development of patchouli cultivation, the main thing that must be known is the characteristics of the plant. In addition, factors supporting the success of patchouli cultivation are also very important, including plant nurseries, land management and planting, maintenance, harvesting and post-harvest handling, and distillation. Planting the patchouli plant is done indirectly by seeding the cuttings first in a nursery. 2) The socio-economic impacts of the patchouli farmer community in Katangana Village are as follows: The social impact of the patchouli farmer community is seen from the social interaction that among patchouli farmers, farm laborers and the community in Katangana Village have a very good relationship such as a sense of unity and brotherhood. The economic impact of the patchouli farmer community has positive and negative impacts on patchouli farmers seen from the income level, it can be explained that the positive impact of patchouli farmers' income in Katangana Village increases because the first and second harvest results are usually the amount or production obtained by the farmers. patchouli farmers increased. While the negative impact obtained from patchouli plants is that during the third harvesting process, patchouli farmers' income usually decreases because the land or land used to plant patchouli is no longer fertile as during the first and second harvesting processes. However, with the income, the patchouli farmers can still meet their daily needs.